Reducing saturated fats in foods - Talbot, Geoff (Woodhead Pub., 2011)
The need to reduce saturated fat levels in food and the different ways of doing this are among the most important issues facing the food industry. Reducing saturated fats in foods reviews the sources and effects of saturated fats in food and the ways in which the food industry can effectively reduce saturates. Part one covers the functional and nutritional aspects of saturated fats in foods, with chapters covering sources of dietary saturated fats, their functional attributes and the health issues associated with saturated fatty acids. Part two focuses on reducing saturated fats through food reformulation, concentrating on both the technologies used and the food categories affected. Chapters cover topics such as emulsion technology for reduction of saturated fats and the application of diacylglycerol oils, as well as different food categories including milk and dairy products, processed meats, fried foods and pastry products. With its distinguished editor and international team of contributors, Reducing saturated fats in foods is an essential reference for oils and fats processors and food manufacturers, as well as those researching saturated fats in the academic sector. Reviews the sources and effects of saturated fats in food and the ways in which the food industry can effectively reduce saturatesExplores the functional and nutritional aspects of saturated fats in foods, covering sources of dietary saturated fats and their functional attributesFocuses on reducing saturated fats through food reformulation, concentrating on both the technologies used and the food categories affected.
Keywords: Saturated fatty acids in human nutrition.; Lipids in human nutrition.; Food -- Fat content.; elektronické knihy; electronic books